2017
DOI: 10.1016/j.ijsu.2017.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer liver metastases in a UK tertiary centre: Outcomes following referral to tumour board meeting

Abstract: Surgical resection of BCLM may improve the overall survival in selected patient groups. This study identifies a cohort of patients, without extrahepatic disease and responsive to chemotherapy, who may particularly benefit from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…We also found that survival was poorer among patients with more extensive systemic disease at diagnosis (P < 0.0001). Similarly, a few aforementioned studies also suggested that patients with liver-only metastatic disease may experience longer survival compared with patients harboring liver metastases in parallel with metastases in other organs (14,15,19,20,48). In a prospective, randomized phase III trial study of 304 women diagnosed with locally advanced (inoperable) or metastatic breast cancer, patients with liver-only metastatic disease experienced longer survival compared with patients harboring liver metastases in parallel with metastases in other organs [log-rank, P ¼ 0.01, multivariate Cox model P < 0.001 adjusting for age (>50 years or 50 years), metastasis-free interval ( 52 years or >2 years); ref .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We also found that survival was poorer among patients with more extensive systemic disease at diagnosis (P < 0.0001). Similarly, a few aforementioned studies also suggested that patients with liver-only metastatic disease may experience longer survival compared with patients harboring liver metastases in parallel with metastases in other organs (14,15,19,20,48). In a prospective, randomized phase III trial study of 304 women diagnosed with locally advanced (inoperable) or metastatic breast cancer, patients with liver-only metastatic disease experienced longer survival compared with patients harboring liver metastases in parallel with metastases in other organs [log-rank, P ¼ 0.01, multivariate Cox model P < 0.001 adjusting for age (>50 years or 50 years), metastasis-free interval ( 52 years or >2 years); ref .…”
Section: Discussionmentioning
confidence: 95%
“…In a retrospective review in 80 consecutive patients who were treated for breast cancer liver metastases, the presence of extrahepatic metastases was found to worsen prognosis in breast cancer liver metastases (HR ¼ 14.21; 95% CI, 1.08-186.94; P ¼ 0.044; ref. 19). As a result, treatment options for liver oligometastases include surgery or stereotactic radiotherapy may hold great value, and more randomized controlled trials are needed to investigate the efficacy of these treatments (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study including 104 BCLM patients concluded that there was no impact of breast cancer subtypes on the survival after hepatic metastases [15]. A single center study of British population also presented similar results [16]. HER2 positive breast cancer is associated with a more aggressive phenotype and worse prognosis.…”
Section: Introductionmentioning
confidence: 75%
“…Patients with primary metastatic diseases have poorer prognosis and benefit less from hepatectomy than those in whom liver metastasis occur more than one year after breast cancer diagnosis [5,8,9]. Despite related criteria of selection of the candidates for hepatectomy in MBC, a few single institution studies report favorable initial results in patients with more than one liver metastases, and more than that, even perform re-resection of hepatic metastases derived from BC [10,11].…”
Section: Discussionmentioning
confidence: 99%